2013
DOI: 10.1007/s10059-013-0139-1
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear FAK: a New Mode of Gene Regulation from Cellular Adhesions

Abstract: Focal adhesion kinase (FAK) is a protein tyrosine kinase (PTK) crucial in regulation of cell migration and proliferation. In addition to its canonical roles as a cytoplasmic kinase downstream of integrin and growth factor receptor signaling, recent studies revealed new aspects of FAK action in the nucleus. Nuclear FAK promotes p53 and GATA4 degradation via ubiquitination, resulting in enhanced cell proliferation and reduced inflammatory responses. FAK can also serve as a co-transcriptional regulator that alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 51 publications
5
67
0
Order By: Relevance
“…Focal adhesion kinase (FAK) is a tyrosine kinase that is linked to cell:extracellular matrix (ECM) signaling [43, 44] and may also exert nuclear functions [45] in both normal and neoplastic cells. We observed that FAK staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Focal adhesion kinase (FAK) is a tyrosine kinase that is linked to cell:extracellular matrix (ECM) signaling [43, 44] and may also exert nuclear functions [45] in both normal and neoplastic cells. We observed that FAK staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such processes can in turn have influence on protein expression, protein interaction, local protein concentration, and intracellular signaling, such as in case of the focal adhesion kinase (FAK). FAK, which upon stimulation at the membrane can induce signal-transduction into the nucleus and gene expression [15,18,19], is known to have strong effects on cell adhesion and migration [20]. Previous studies exploiting a similar ''biochip''-setup in our group have indeed shown an effect of topographies on osteoblast focal adhesions [21].…”
Section: Discussionmentioning
confidence: 81%
“…These findings are crucial since the activation of the FAK pathway is described to be involved in survival mechanisms, and especially in a variety of distinct cancer cell lines’ development and metastasis [41,42]. Indeed, FAK regulates numerous downstream intracellular pathways that mediate either cell migration through actin modification [43] or cell proliferation through transcription factors [44]. Interestingly, in HT29 cells, both the actin cytoskeleton and mitogen-activatd protein (MAP) kinases are regulated by sSortilin/NTSR3.…”
Section: Signaling Of Ssortilin/ntsr3 In Ht29 Cellsmentioning
confidence: 99%